Two bronze seals related to the Mongolian Empire and Ming dynasty - Lkhagvadorj, Munnkhhbayar; Byambadorj, Bat-Erdene; Gonchig, Batbold (Studia Archaeologica, 2022)
The purpose is to determine the exact dates of the two bronze seals kept in the museum fund of Uvurkhangai aimag and to consist of them into our research. On or after reading the Chinese inscriptions on these two seals, it became clear that these seals were important documents in the history of Mongolia during the Mongol Empire and its aftermath, also, especially during the Ming Dynasty. The first seal dated the first year of Huang-ch’ing 皇慶 [1312] remains the administrative official seal of the Judicial proceeding office one of the special units of Ling-bei Province during the Yuan Dynasty, (the administrative and governments unit occupied approximately the area of present-day Mongolia), was it first found and identified in Mongolia. The second seal dated the first year of Yong-Le [1403] an army seal of the header of the centurion family “Xing zhou” one of the special military organizations during the early Ming dynasty. Монголын эзэнт гүрэн болон Мин улсын үед холбогдох хоёр хүрэл тамга Товчлол. Өвөрхангай аймгийн музейн сан хөмрөгт хадгалагдаж буй хоёр хүрэл тамганы он цагийг нарийвчлан тогтоож, судалгааны эргэлтэд оруулахыг зорилоо. Тус тамганууд дээр буй нангиад бичээсний уншлагаас үзвэл энэхүү тамганууд Монголын эзэнт гүрний хийгээд түүний дараахан үеийн монголын түүхийн чухал баримт болох нь тодорхой болов. Түлхүүр үгс: Хүрэл тамга, Юань гүрэн, Давааны арын муж, Линбэй, Мин улс, Шин жоу